Strategi Promosi Dinas Perpustakaan dan Kearsipan Kabupaten Padang Lawas - Rahmi Pakpahan, Anita; Sazali, Hasan; Purwaningtyas, Franindya (IAI Nasional Laa Roiba Bogor, 2024)
This research was conducted at the Department Libraries And Archives Padanglawas Regency which aims to determine the promotion strategy Service Libraries And Archives Padang Lawas Regency in increasing interest visit, as well as what obstacles just Which felt in do activity promotion. The method used in this research is a qualitative method using a descriptive approach with make description of the data that has been collected as exist. As for data collection techniques carried out in this study were interviews, observation and documentation. Determination of informants is done by the method purposive sampling. The informant of this research is the Head of Service Libraries And Archives Padanglawas Regency along head of department library and librarian. The results of this study indicate that the library promotion strategy in increase interest visits made library that is with stage Socialization in the library, library tours, exhibitions, spread brochures, newspapers or newspapers, promotions with social media. While the constraints felt that the funds minimal, lack of cooperation and lack of public awareness about the importance of libraries. Keywords: Promotion, Strategy Promotion, Promotion Library